Effect of double cleavage stage versus sequential cleavage and blastocyst stage embryo transfer on clinical pregnancy rates - Gozde Kaya; Begum Alyürük; Ozge Senem Yucel Cicek; Sule Yildirim Köpük; Ahmet Yigit Çakiroğlu; Emek Doğer; Serdar Filiz (Asian Pacific Journal of Reproduction, 2020)
Objective: To compare clinical pregnancy rates following sequential day-3 and day-5 embryo transfer with double or sequential cleavage-stage transfers. Methods: This study enrolled 242 patients undergoing gonadotropin-releasing hormone antagonist protocol and fresh embryo transfer. Basal follicle stimulating hormone, luteinizing hormone, serum estradiol and anti-Müllerian hormone levels and controlled ovarian stimulation outcomes were noted. Of 242 women, 135 underwent double embryo transfer on day 2 or day 3 (the double group), 54 women underwent sequential embryo transfer on day 2 and day 3 (the D2/D3 group), and 53 underwent sequential embryo transfer on day 3 and day 5 (the D3/D5 group). Clinical pregnancy rates were compared among the groups. Results: Female age, body mass index, basal follicle stimulating hormone, luteinizing hormone and estradiol levels were similar among the groups (P>0.05). The D3/D5 group had a significantly higher number of metaphase II oocytes, fertilized oocytes and good quality embryos on day 3 compared with the double group and the D2/D3 group (P < 0.001). Clinical pregnancy rates in the double, D2/D3 and D3/D5 groups were 26.6% (36/135), 16.6% (9/54) and 37.7% (20/53), respectively. There was no significant difference in clinical pregnancy rates between the double group and the D2/D3 group (P =0.204) or the D3/D5 group (P =0.188). The D3/D5 group had significantly higher clinical pregnancy rates compared with the D2/D3 group (P =0.025). Conclusions: Sequential cleavage-stage transfer (D2/D3) or cleavage stage and blastocyst transfer (D3/D5) does not improve clinical pregnancy rates compared with double cleavage-stage embryo transfer. Although sequential transfer seems to be an effective option in certain patient populations, routine application of this technique might not be a suitable approach in an unselected population to improve assisted reproductive technology outcomes.